SOME ISSUES OF THE ORGANIZATION OF ICE TOURISM DESTINATIONS IN UZBEKISTAN - Asror Nizamov; Nodira Sultonova; Akmal Matnazarov; Adilbek Risbekov (The Bioscan, 2024)
This article is devoted to the issues of organizing glacitourism routes in the territory of the Republic of Uzbekistan, the article elaborates a number of recommendations on the organization of glacitourism routes in our republic and highlights the level of complexity based on the possibility of exiting the routes.